A Regioselective Synthesis of Aryl Sulfones Using Graphite/MeSO3H (GMA) - Hosseini-Sarvari, Mona (Letters in Organic Chemistry, 2008)
A rapid, high yielding and regioselective process has been developed for the synthesis of aryl sulfones via sulfonation reactions using a mixture of graphite/MeSO3H.
Keywords: Graphite